2015
DOI: 10.5604/12321966.1167729
|View full text |Cite
|
Sign up to set email alerts
|

Realities of ambulatory multi-drug treatment of chronic diseases in rural areas of Lublin Province, eastern Poland – comparison of situations in 2010 and 2013

Abstract: Introduction. The economic stratification observed for many years among the population in Poland, increasing poverty rates, especially those being effects of the current economic crisis in the country, and the rising prices of medicines, are potential risk factors for medication non-adherence among patients in the poorest class of the Polish population. Materials an method. The subjects were 2 groups of inhabitants of rural areas of Lublin Province in eastern Poland. The first consisted of 209 people aged 52-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The study showed that the majority of forestry workers experience musculoskeletal complaints, most frequently low back pain, pain concerning the knees, and the regions of the neck and shoulders. A similar scale of the phenomenon of the occurrence of musculoskeletal complaints was found in studies conducted among private farmers [17,18]. A high level of occurrence of musculoskeletal disorders among the examined foresters is certainly associated with a large number of employees at an older age, with a long period of employment, or working under difficult conditions.…”
Section: Discussionmentioning
confidence: 52%
“…The study showed that the majority of forestry workers experience musculoskeletal complaints, most frequently low back pain, pain concerning the knees, and the regions of the neck and shoulders. A similar scale of the phenomenon of the occurrence of musculoskeletal complaints was found in studies conducted among private farmers [17,18]. A high level of occurrence of musculoskeletal disorders among the examined foresters is certainly associated with a large number of employees at an older age, with a long period of employment, or working under difficult conditions.…”
Section: Discussionmentioning
confidence: 52%
“…We grouped variables to see how they related to both biological rhythm patterns and self-harm. Based on prior research's findings, we thought about age, sex, ethnicity, financial difficulties, family support, and adverse life events as possible potential covariates [14,22,38,43,50].…”
Section: Covariatesmentioning
confidence: 99%